Incidencia del periodismo ambiental en las grandes audiencias con mujeres que laboran en actividades agrícolas en la Parroquia El Vergel del cantón Valencia, año 2022 - Valverde Vera, Mirko (2022)
Environmental journalism was born from the need to document each of the existing problems in the environment as a result of the harmful hand of man, which needed to be public knowledge to make each of the inhabitants known to raise awareness among the inhabitants. , since the environmental issue is of the utmost importance since the negative effect of it harms everyone. Environmental communication was born in the 19th century with the appearance of environmental activist movements that sought to document environmental deterioration. For this reason, the objective of this research is to determine the incidence of environmental journalism in the audiences of women who work in agricultural activities in the parish "El Vergel", Cantón Valencia year 2021. In turn, it is concluded that there are a large number of shortcomings within the agricultural activity within the El Vergel enclosure, keeping the staff in precarious conditions, for this reason environmental documentation is needed to correct these shortcomings.